Implementasi Sistem Cash Flow Management Digital untuk Meningkatkan Kesehatan Keuangan UMKM di Kelurahan Batu Besar, Kota Batam - Putriyani Anjelina Hutapea; Jesikka Nadia Putri; Anggi Nanda Syahrani; Yati Salma; Dailimi Dailimi; Rica Fitri Susanti UE; Mohamad Hisam; Dewi Permata Sari; Muhammad Sapuan (CV. Aksara Global Akademia, 2026)
Micro, Small, and Medium Enterprises (MSMEs) play a vital role in strengthening the national economy. However, limited financial literacy and weak cash flow management remain major challenges among MSME actors. This community service program aimed to improve the financial health of MSMEs in Batu Besar Village, Nongsa District, Batam City through the implementation of a digital cash flow management system using FinSense AI. The program was conducted through four stages, namely preliminary assessment, financial literacy education, digital application implementation, and mentoring. The activities involved 34 MSME actors from various business sectors. The results indicated an improvement in participants' understanding of business cash flow, financial planning, transaction recording, and business cash sustainability. Participants were able to separate personal and business finances more effectively and utilize digital technology to monitor financial performance. The implementation of a digital cash flow management system provided practical benefits in supporting decision-making, reducing financial recording errors, and strengthening financial discipline. The program demonstrates that digital financial technology can be an effective tool for improving MSME financial resilience and supporting sustainable business growth